Introduction to Adventist Mission - Doss, Gorden R. (Department of World Mission Sevent-Day Adventist Theological Seminary Andrews University Institute of World Mission General Conference of Seventh-Day Adventists, 2018)
The first of its kind in Seventh-day Adventist scholarship, this book is an excellent introduction to Christian mission from an Adventist perspective. The book addresses mission comprehensively, including biblical foundations, theology of mission, history of mission, contextualization for mission, strategies for mission, and other topics.